Crowdfunding in the production of video games in Spain: Evolution and success on Kickstarter. - Victoria-Mas, Juan Salvador; Ramos-Ábalos, Eva María; Arjona-Martín, José Borja (Universidad de Navarra, 2023)
This research addresses the use of crowdfunding platforms forthe development of video games in Spain. It is part of the group ofplatform-centred research in order to develop a quantitativeanalysis of the data contained in them. Specifically, the dataprovided by Kickstarter for Spanish video game developmentprojects is analysed. Normality tests indicated that the variables donot follow a normal distribution, hence non-parametric tests wereused. The success rate of Spanish campaigns is 28.4% for the totalnumber of cases, 40.8% in 2020, which is a steady growth since2015. The average funding is €16,586.76, €50,056.67 for successfulcampaigns; however, the median indicates that 50% of the sampledoes not exceed €1,653 in funding. Regression models are used todevelop equations to calculate the amount of funding needed topublish on PC and console, and the number of backers needed toachieve a given amount of funding.
https://revistas.unav.edu/index.php/communication-and-society/about: Communication & Society provides open access to all published content, to facilitate its dissemination and promote research, supporting an exchange of knowledge.
Keywords: Videojuegos; Industria audiovisual; Economía colaborativa; Crowdfunding